2006
DOI: 10.1002/pssc.200563116
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption of ferrite powders in a polymer matrix

Abstract: The object of this work is to investigate the microwave absorbing properties of nanocomposite bulk samples. As filler we used magnetite with different particle size in a silicone rubber matrix and investigated the influence of the filler concentration and particle size in the polymer matrix on the microwave nonlinearity in a large frequency range (1 ÷ 13 GHz). We found that the intensity and the frequency at the reflection loss minimum depend on the particle size and particle concentration of magnetite in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…4a, the real parts of complex permittivity almost keep constant in the measured frequency range. And their values are comparatively smaller than those observed for the metal powder [18][19][20] reported in literatures. The lower real part of complex permittivity is a great advantage to strike a balance between permeability and permittivity, thus decreasing the reflection coefficient of the absorber compared with those metal powders.…”
Section: Magnetic Propertiescontrasting
confidence: 77%
“…4a, the real parts of complex permittivity almost keep constant in the measured frequency range. And their values are comparatively smaller than those observed for the metal powder [18][19][20] reported in literatures. The lower real part of complex permittivity is a great advantage to strike a balance between permeability and permittivity, thus decreasing the reflection coefficient of the absorber compared with those metal powders.…”
Section: Magnetic Propertiescontrasting
confidence: 77%
“…Low coercivity and high saturation magnetization of nickel ferrite are also significant for obtaining good absorption properties. It has been reported that in the nanoregime, the dielectric permittivity and magnetic permeability of ferrites gets considerably modified with respect to their ceramic counterparts because of their high surface to volume ratio [2][3][4][5]. Hence incorporation of nickel ferrite nanoparticles into a matrix like natural rubber can result in an excellent microwave absorbing material.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrites of different composition have been widely studied because of their potential in finding numerous applications in electronic devices [2][3][4][5]. There is an increasing demand for cost effective electromagnetic absorber technology with minimal electromagnetic pollution and electromagnetic interferences.…”
Section: Introductionmentioning
confidence: 99%
“…5a, the real parts of complex permittivity decrease slightly with the increasing frequency. And their values are comparatively smaller than those of metal powders reported in the literatures [19,20]. The lower real part of complex permittivity is a great advantage to strike a balance between permeability and permittivity, thus decreasing the reflection coefficient of the absorber compared with other metal magnetic materials for microwave-absorbing application [16].…”
Section: Resultsmentioning
confidence: 86%